Relationship between periodontitis and COVID‐19: A bidirectional two‐sample Mendelian randomization study - Jukun Song; Yadong Wu; Xinhai Yin; Junmei Zhang (Health Science Reports, 2023)
Abstract Background and Aims Coronavirus disease (COVID‐19) is a major danger to world health and has been linked to periodontitis in a number of epidemiological observational studies. However, it is unclear whether COVID‐19 causes periodontitis. COVID‐19's causal influence on periodontitis was determined using bidirectional Mendelian randomization (MR). Methods Large‐scale COVID‐19 and periodontitis genome wide association study data were analyzed. Inverse variance weighting, MR‐Egger, weighted median, and MR‐PRESSO were used to estimate causal effects. Sensitivity studies were conducted using the Cochran's Q test, the MR‐Egger intercept test, the MR‐PRESSO, and the leave‐one‐out (LOO) analysis. Further investigation of potential mediating factors was performed using risk factor analysis. Results The MR presented no causal relationship between periodontitis and hospitalization for COVID‐19 (odds ratio [OR] = 0.97, 95% confidence interval [CI] 0.78–1.20; p = 0.76), vulnerability to COVID‐19 (OR = 1.04, 95% CI 0.88–1.21; p = 0.65), COVID‐19 disease severity (OR = 1.01, 95% CI 0.92–1.11; p = 0.81). Meanwhile, a noncausal effect of genetic hospitalization for COVID‐19, illness severity, and vulnerability to periodontitis was detected. Other MR methods yielded identical results to inverse variance weighting. According to sensitivity analysis, horizontal pleiotropy is unlikely to affect causal estimation. Conclusion Periodontitis had no link to the risk of COVID‐19 hospitalization, susceptibility, or severity. However, the substance in COVID‐19 that is responsible for this effect must be studied further.